The framework for systematic reviews on psychological risk factors for persistent somatic symptoms and related syndromes and disorders (PSY-PSS) - Hüsing, Paul; Smakowski, Abigail; Löwe, Bernd; Kleinstäuber, Maria; Toussaint, Anne; Shedden-Mora, Meike C. (Frontiers in Psychiatry, 2023)
Introduction: Numerous psychological factors are believed to play a pivotal role in the development and maintenance of persistent somatic symptoms (PSS) in all fields of medicine. However, very few of these factors have been empirically investigated in relation to PSS. The aim of this study is firstly to propose a framework and define search terms for systematic reviews on the empirical evidence and diagnostic value of psychological risk factors for PSS and PSS-related outcomes (PSY-PSS). Secondly, the application of the framework is illustrated using the example of a systematic review on the relevance of psychological factors in somatic symptom disorders (SSD; DSM-5) and bodily distress disorders (BDD; ICD-11). Methods: Following a narrative review approach, two comprehensive lists of search terms to identify studies in 1) relevant patient groups with PSS and 2) relevant psychological factors were generated by reviewing the current literature and employing an iterative process of internal revision and external expert feedback. Results: We identified 83 relevant symptoms, syndromes and disorders for which we defined a total of 322 search terms (list 1). We further comprised 120 psychological factors into 42 subcategories and 7 main categories (list 2). The introduced lists can be combined to conduct systematic reviews on one or more specific psychological factors in combination with any symptom, syndrome or disorder of interest. A protocol of the application of this framework in a systematic review and meta-analysis on psychological etiological factors of SSD and BDD is presented following the PRISMA guidelines. Discussion: This framework will help to gather systematic evidence on psychological factors in order to improve the understanding of the etiology of PSS, to refine future diagnostic conceptualizations of PPS, and to develop optimized mechanism-based interventions for individuals with PPS and related syndromes and disorders.